Differences in the Effect of Giving Fe Tablets and Capsules Moringa Leaves on Hepcidin and Ferritin Levels in Anemic Pregnancy Rats - Novita Sari; Delmi Sulastri; Endrinaldi Endrinaldi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Anemia is a condition characterized by a decrease in Hemoglobin (HB), a serious global public health problem especially affecting children and pregnant women. This study aimed to determine differences in the effect of giving Fe tablets and capsules of Moringa leaves on hepcidin and ferritin levels in anaemic pregnancy rats. This research was an experimental study with a randomized post-test-only control group design. This research was conducted at the Animal House of the Faculty of Medicine, Andalas University to maintain and treat experimental animals. Ferritin and Hepcidin examinations were carried out at the biomedical laboratory of the Faculty of Medicine, Andalas University. The sample in this study were female white rats (Rattus Novergicus) which met the inclusion and exclusion criteria, the data were analyzed using One Way Anova. The results of this study indicated that the mean hepcidin levels in the Fe (P1) and Moringa leaf capsule (P2) groups were 181.902 ± 20.31 and 216.362 ± 29.90 with a p-value of 0.006 . The mean ferritin levels in the Fe(P1) and Moringa leaf capsule (P2) groups were 1.928 ± 0.263 and 2.308 ± 0.320 with a p-value of 0.004. The conclusion in this study was that there was an effect on hepcidin levels after being given Fe tablets (P1) and Moringa leaf capsules (P2) to anemic pregnant rats and there was an effect on ferritin levels after being given Fe tablets (P1) and Moringa leaf capsules (P2) to anemic pregnant rats Keyword: Anemic, Ferritin, Fe Tablets, Hepcidin, Moringa Leaf Capsules